Eating behaviour traits mediate the association between satiety responsiveness and energy intake among individuals with overweight and obesity. (1st January 2023) - Jacob, Raphaëlle; Provencher, Véronique; Panahi, Shirin; Tremblay, Angelo; Drapeau, Vicky
Abstract: Whether eating behaviour traits represent factors that could explain the susceptibility to overeating in individuals with low satiety responsiveness remain to be extensively examined. This study aimed to assess if eating behaviours mediate the association between satiety responsiveness and energy intake. Baseline data from individuals with overweight or obesity (n = 303; age = 38.7 ± 8.4 years; BMI = 33.2 ± 3.4 kg/m 2, 56% women) who participated in four weight-loss studies were included in this cross-sectional study. Satiety responsiveness was determined by the satiety quotient (SQ) based on fullness sensations in response to a standardized breakfast. Energy intake was self-reported in a three-day food record and measured by an ad libitum buffet meal. Eating behaviours were assessed with questionnaires. Mediation analyses adjusted for age and sex, and for underreporting for the food record, were performed using a regression-based and bootstrapping approach. The association between SQ and self-reported total energy intake was mediated by susceptibility to hunger (β = −2.51 ± 1.26, 95% CI, −5.38 to −0.52) and its subscales, internal and external locus of hunger (β = −2.00 ± 1.10, 95% CI, −4.50 to −0.28 and β = −2.42 ± 1.29, 95% CI, −5.30 to −0.30, respectively). Susceptibility to hunger (β = −2.71 ± 1.13, 95% CI, −5.29 to −0.84), internal and external locus of hunger (β = −1.84 ± 0.95, 95% CI -4.00 to −0.30 and β = −3.42 ± 1.31, 95% CI, −6.39 to −1.24, respectively), cues that may trigger food cravings (β = −5.43 ± 2.91, 95% CI, −11.83 to −0.44) and state-craving as a physiological state (β = −4.31 ± 2.51, 95%CI, −10.14 to −0.44) also mediated the association between SQ and measured energy intake. These results suggest that susceptibility to hunger and food cravings partly explained the susceptibility to overeating among individuals with low satiety responsiveness. Interventions targeting susceptibility to hunger and food cravings may thus be helpful to prevent overeating among these individuals.